Tropical Palm Endophytes Exhibit Low Competitive Structuring When Assessed Using Co-occurrence and Antipathogen Activity Analysis - Donald, Julian; Barthélemy, Morgane; Gazal, Nina; Eveno, Yannick; Manzi, Sophie; Eparvier, Véronique; Stien, Didier; Roy, Mélanie (Frontiers in Forests and Global Change, 2019)
Leaf-inhabiting fungal and bacterial endophytes are at their most diverse in tropical rainforest plant hosts, with some influencing host plant fitness as either symbionts or pathogens. Endophyte activity and community composition is thought to depend on competition amongst co-occurring species for resources. Here, we attempt to reveal the strength of competitive interactions between endophytes by combining e-DNA metabarcoding to characterize the community with culturing assays to ascertain their potential activity. The endophyte community associated with the understory palm Astrocaryum sciophilum was determined by extracting eDNA from 120 leaflets of eight plants located in a lowland rainforest of French Guiana. This revealed 516 fungal and 606 bacterial OTUs. Co-occurrence analysis of the most abundant OTUs revealed that direct fungal-fungal interactions were overall more negative than bacterial-bacterial interactions. This was confirmed by C-score calculations for the whole endophyte community, which revealed significantly greater levels of species segregation for fungi but not bacteria when compared with simulated random communities. Following the culturing of 131 fungal, and 66 bacterial Astrocaryum endophytes collected from the same leaves, Minimal Inhibitory Concentrations of ethyl acetate culture extracts were evaluated against the fungus Trichophyton rubrum and the bacterium Staphylococcus aureus. Overall, a minority of extracts demonstrated antipathogen activity, with greater antifungal activity expression for both fungi and bacteria when compared with antibacterial activity. In order to explore whether this activity translated into competitive structuring of the observed community, a BLAST was conducted to match metabarcoding sequences with Sanger derived culture sequences. This demonstrated that cultures displaying antipathogen activity were significantly more likely to co-occur with fungi if they were bacteria and bacteria if they were fungi. Nevertheless, overall correlation values averaged around zero. These results indicate that for Astrocaryum palms, fungal endophytes are likely to play a greater role in determining colonization success of subsequent endophytes whether these be fungal or bacterial, but that overall endophyte communities do not display strong patterns of community structuring through competition. Endophyte communities are thus likely to reach relative stasis in mature leaves, where the diverse community of fungi and bacteria and plant traits prevent the subsequent establishment of pathogens.